Correlation between carcass sides meatness and ultrasound measures on live pigs - Senčić, Đuro; Šperanda, Tomislav; Šperanda, Marcela; Antunović, Zvonko (Acta Agraria Kaposváriensis, 2002)
Correlation (r) between carcass sides meatness, determined by the Regulations («two points« method) and by dissection, and bacon thickness and musculus longissimus dorsi (MLD) measured at various places (between 10th and 11th rib, behind the last rib, in the middle of the loins and at the sacrum) by an ultrasound device on live pigs (n = 60) at their body weight of approximately 100 kg was investigated. Bacon thickness on the small of the back (r = -0.85 and r = -0.75) was determined to be the best indicator the sides meatness and potential selection criteria.